Spatial Analysis of Dengue Hemorrhagic Fever Cases with Rainfall and Humidity as Influencing Factors in DKI Jakarta Province 2020 - Astika Azhari Utomo; Arifa Rahma Izzati; Gita Fitri Cahyani; Fathonah Sholihah Farizal; Gitri Syiamil; Hasna Khalishah; Shelvira Afifah; Muhammad Gozi Ataya; Agung Saputra (UHAMKA Press, 2020)
Background: DKI Jakarta is included in the 10 provinces in Indonesia with the highest number of dengue cases. Physical environmental conditions, such as humidity and rainfall, are one of the risk factors that can affect the increase in the incidence of dengue cases. Objectives: The purpose of this study was to determine the effect of rainfall and humidity factors on the incidence of Dengue Hemorrhagic Fever (DHF) in DKI Jakarta Province on the first three months of 2020. Method: The research sample in the form of rainfall and humidity data from January to March 2020 was obtained from the Meteorological, Climatological, and Geophysical Agency (known as BMKG) online data and DKI Jakarta’s Central Bureau of Statistics (known as BPS) website. The method of spatial analysis are conducted using GIS software, QGIS version 3.16.4. Statistical analysis was conducted using IBM SPSS 22 software. Result: The results of statistical analysis using the Pearson correlation test showed that both variables have no significant correlation with number of DHF cases (p-value > 0.05). The conclusion is that the level of rainfall and humidity in the first 3 months of 2020 is not related significantly to the number of dengue cases, because there are many other factors influencing the DHF condition itself. Conclusion: This situation can happen because there are so many factors that influence the incidence of DHF itself. The incidence of DHF can be influenced by factors such as population mobility, changes in population density and distribution, as well as many other epidemiological factors that still need to be investigated.